Madaras & Sorelle, Eds., Taking Sides - Clasing Views On Controversial Issues In American History Vol II - Reconstruction To Present - Harvey, Gordon (Teaching History: A Journal of Methods, 2001)
Whenever a text reaches its eighth edition, one must assume that the editors are doing something right. Such is the case with Taking Sides. The editors have tried to strike that ever-elusive balance between social, diplomatic, and political history. They have accomplished this goal as well as anyone else.